H-Bonding assisted self-assembly of anionic and neutral ligand on metal: a comprehensive strategy to mimic ditopic ligands in olefin polymerization - Mote, Nilesh R.; Patel, Ketan; Shinde, Dinesh R.; Gaikwad, Shahaji R.; Koshti, Vijay S.; Gonnade, Rajesh G.; Chikkali, Samir H. (Inorganic Chemistry, 2017)
Self-assembly of two neutral ligands on a metal to mimic bidentate ligand coordination has been frequently encountered in the recent past, but self-assembly of an anionic ligand on a metal template alongside a neutral ligand remains an elusive target. Such a self-assembly is hampered by additional complexity, wherein a highly negatively charged anion can form intermolecular hydrogen bonding with the supramolecular motif, leaving no scope for self-assembly with neutral ligand. Presented here is the self-association of anionic ligand 3-ureidobenzoic acid (2a) and neutral ligand 1-(3-(diphenylphosphanyl)phenyl)urea (1a) on a metal template to yield metal complex [{COOC6H4-NH(CO)NH2}{Ph2PC6H4NH(CO)NH2}PdMeDMSO] (4a). The identity of 4a was established by NMR and mass spectroscopy. Along the same lines, 3-(3-phenylureido)benzoic acid (2b) and 1-(3-(diphenylphosphanyl)phenyl)-3-phenylurea (1b) self-assemble on a metal template to produce palladium complex [{COOC6H4NH(CO)NHPh}{Ph2PC6H4NH(CO)NHPh}PdMePy] (5c). The existence of 5c was confirmed by Job plot, 1-2D NMR spectroscopy, deuterium labeling, IR spectroscopy, UV-vis spectroscopy, model complex synthesis, and DFT calculations. These solution and gas phase investigations authenticated the presence of intramolecular hydrogen bonding between hydrogen's of 1b and carbonyl oxygen of 2b. The generality of the supramolecular approach has been validated by preparing six complexes from four monodentate ligands, and their synthetic utility was demonstrated in ethylene polymerization. Complex 4a was found to be the most active, leading to the production of highly branched polyethylene with a molecular weight of 55700 g/mol and melting temperature of 112 degrees C.